2020
DOI: 10.1093/ecco-jcc/jjaa049
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gut-Selective Pan-Janus Kinase Inhibitor TD-1473 for Ulcerative Colitis: A Translational Medicine Programme

Abstract: Background and Aims Oral systemic pan-Janus kinase [JAK] inhibition is effective for ulcerative colitis [UC] but is limited by toxicities. We describe preclinical to clinical translation of TD-1473—an oral gut-selective pan-JAK inhibitor—from in vitro characterization through a Phase 1b study in patients with UC. Methods TD-1473 JAK inhibition potency was evaluated in vitro; plasma pharmacokinetics, safety and efficacy were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 18 publications
2
73
0
Order By: Relevance
“…The use of tezepelumab, an antibody against TSLP in adults with uncontrolled asthma, suggest that selective JAK2 inhibition might be beneficial 47 . In addition, given the potential side effects of systemic JAKis, other localized routes of administration of JAKis with unique biophysical properties (such as those restricted to the gut, or topical or inhaled routes) may be beneficial in intestinal 48 , dermatological 49 , 50 or respiratory 33 diseases, although determining the dosing regimens may be challenging and it is not clear whether partial inhibition of systemic JAKi is sufficient in all of these indications 49 , 50 .…”
Section: Jaks and Tyk2mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of tezepelumab, an antibody against TSLP in adults with uncontrolled asthma, suggest that selective JAK2 inhibition might be beneficial 47 . In addition, given the potential side effects of systemic JAKis, other localized routes of administration of JAKis with unique biophysical properties (such as those restricted to the gut, or topical or inhaled routes) may be beneficial in intestinal 48 , dermatological 49 , 50 or respiratory 33 diseases, although determining the dosing regimens may be challenging and it is not clear whether partial inhibition of systemic JAKi is sufficient in all of these indications 49 , 50 .…”
Section: Jaks and Tyk2mentioning
confidence: 99%
“…TYK2 pseudo-kinase inhibitors have shown that using human genetics with the analysis of rare coding variants enables both the identification and the design of novel drug targets 51 . Improving organ-specific (such as gut, lung or skin) 48 and/or cell-specific 261 delivery of kinase inhibitors should also improve therapeutic efficacy with reduced side effects.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…TD-1473 is an oral pan-JAK inhibitor that is designed to be gut specific to limit systemic toxicity of pan-JAK inhibition. In a phase 1b trial, patients with moderate to severe UC (n 40) were assigned to placebo or one of the following once daily TD-1473 doses: 20 mg, 80 mg or 270 mg) for 28 days (Sandborn et al, 2020f). Only five of the 40 patients were exposed to anti-TNF therapies in the past.…”
Section: Td-1473mentioning
confidence: 99%
“…Only five of the 40 patients were exposed to anti-TNF therapies in the past. Clinical response rate was 20% in the 20 and 80 mg groups compared to 55% in the 270 mg group while the clinical response rate was 11% in the placebo group (no statistical analyses performed as study not powered for outcomes) (Sandborn et al, 2020f). There were also trends in endoscopic improvement along with reduction in fecal calprotectin and c-reactive protein (CRP) levels with TD-1473.…”
Section: Td-1473mentioning
confidence: 99%
“…Subjects were randomized to receive 20 mg, 80 mg, 270 mg or placebo for four weeks. TD-1473 yielded high intestinal ( vs plasma) drug concentrations and showed trends towards reduced levels of clinical, endoscopic and histological disease activity [ 48 ]. A further phase IIb/III set of studies are underway to evaluate the use of TD-1473 in the induction and maintenance of subjects with UC (NCT03758443).…”
Section: Other Moleculesmentioning
confidence: 99%